2014
DOI: 10.1002/cb.1488
|View full text |Cite
|
Sign up to set email alerts
|

Identifying factors that promote consumer behaviours causing expired domestic food waste

Abstract: Many commentators argue that domestic food waste is strongly influenced by consumer behaviours. This article reports on a study using mixed‐methods to identify key factors responsible for promoting consumer behaviours that lead to domestic food waste through the lens of the value–belief–norm theory. On the basis of the study's findings, three factors are proposed that cause behaviours that lead to food waste: supply knowledge – does a consumer know what food they have available; location knowledge – does a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
202
2
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(240 citation statements)
references
References 20 publications
(36 reference statements)
11
202
2
7
Order By: Relevance
“…Consumers' food waste behaviors are directly related to planning and shopping routines [50], having or lacking an overview of stocks, having or lacking knowledge about whether food can still be used and situational influences (e.g., specific purchase or consumption contexts; [51]). A diary study in Finland identified that gender, household composition, belief in packaging and perception of the "value of money" at purchase influence food waste [52], while it was mainly young, male and single consumers in research in Portugal [53] that wasted more food.…”
Section: Consumer Behavior Research Regarding Food Wastementioning
confidence: 99%
“…Consumers' food waste behaviors are directly related to planning and shopping routines [50], having or lacking an overview of stocks, having or lacking knowledge about whether food can still be used and situational influences (e.g., specific purchase or consumption contexts; [51]). A diary study in Finland identified that gender, household composition, belief in packaging and perception of the "value of money" at purchase influence food waste [52], while it was mainly young, male and single consumers in research in Portugal [53] that wasted more food.…”
Section: Consumer Behavior Research Regarding Food Wastementioning
confidence: 99%
“…Beyond these basic factors, several studies and surveys have found that consumers' culinary skills and, more generally, information and awareness on the wider implications of food (e.g., nutritional properties and related dietary effects, conditions of safe use, cultural aspects, social and environmental implications) have a positive correlation with a reduced generation of FW in the households, since they contribute to create a positive attitude towards good practices at different levels: planning of food shopping and meals at home, food storage, meal preparation and portioning, reuse of leftovers and optimisation of food available at home, donation of the food that cannot be consumed for any reason, and sorting of kitchen waste [13][14][15]17,22,25,104,134,147,153,154,158,[175][176][177].…”
Section: Fw Drivers Related To Consumers' Individual Behaviours Modifmentioning
confidence: 99%
“…Téma týkající se plýtvání potravinami je nutno chápat jako globální problém (na jedné straně plýtvání potravinami a na druhé straně pro řadu lidí nedostatek nebo nedostupnost potravin). (Butler, 2012, Evans, 2011, Farr-Wharton, et. al.…”
Section: Plýtvání-globální Problém: Nadbytek Versus Nedostatek Potravinunclassified